DAMPAK KETERBATASAN SUMBER DAYA TERHADAP KUALITAS PEMBELAJARAN DI SEKOLAH DASAR - Rahmilawati Ritonga; Ade Kurnia Sari; Amelia Alifah Sagala; Miftahul Aisyiyah Bakti; Ayu Fadhilah Yunanda; Clara Sati Amelia (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study is a literature study that aims to find and analyze the impact of scarce resources on teaching standards in elementary schools in Indonesia. identify and analyze the impact of limited resources on the quality of learning in elementary schools (SD) in Indonesia. These resources include human resources such as the number and quality of teachers; financial resources such as the funding needed for educational operations; and physical resources such as the availability of classrooms, facilities, equipment, and learning materials. The fact that many elementary schools are still struggling to meet the basic requirements of education, especially in rural and poor areas, is what drives this study. The effectiveness of the learning process is significantly affected by scarce resources, according to an analysis of various literature, scientific articles, and research reports published in the last ten years. Low student engagement, reduced willingness to learn, lack of diversity in learning strategies, and poor learning outcomes are direct consequences of this shortage. In addition, there is an imbalance in the teacher-student ratio and a decrease in the intensity of classroom teaching due to the shortage of skilled teachers. This study also emphasizes the importance of government and education stakeholders' efforts to close the resource gap, whether in the form of increased education funding, teacher preparation programs, or technological advancements in the classroom. As a result, the standard of teaching in primary schools can be significantly and equitably improved. This study significantly helps the development of primary education policies that support equitable education quality throughout Indonesia and are more sensitive to the actual situation on the ground.